Systemic resistance to methotrexate in transgenic mice carrying a mutant dihydrofolate reductase gene. - Isola, L M (1986)
A full-length cDNA coding for a mutant dihydrofolate reductase (DHFR; 5,6,7,8-tetrahydrofolate: NADP+ oxidoreductase, EC 1.5.1.3), cloned from a mouse fibroblast cell line grown in high concentrations of methotrexate (MTX), was microinjected into mouse embryos to produce transgenic mice. The DHFR cDNA product is 270-fold more resistant to MTX than the wild-type enzyme. Seventeen transgenic mouse lines, identified by Southern blotting of tail or spleen DNA, carried between 1 and 400 copies of the foreign gene per cell. Eight lines have thus far been tested for resistance to MTX. Control mice were treated until death; MTX was withdrawn from transgenic mice when a cumulative MTX dose uniformly fatal for controls was reached. The major site of MTX toxicity was the gastrointestinal tract, with death of controls resulting from fluid and weight loss. Transgenic animals were relatively resistant to these symptoms and tolerated significantly more MTX than control animals. These results show that genes conferring resistance to chemotherapeutic agents can, after transfer into intact organisms, produce systemic drug resistance.